AdvancED game design with Flash - Van der Spuy, Rex (Advanced series., 2010)
Creating games in Flash is a never-ending journey of exploration, learning, and most of all, fun. Once you've mastered the basics, a new world is opened up to you, enabling you to take your existing skills to the next level and discover new skills that will in turn open new doors. This book is a direct continuation of Foundation Game Design with Flash, and is a complete point-by-point roundup of the most important skills a Flash game designer needs to know. You'll increase your ActionScript knowledge and your game design skills while creating some excellent example games. You'll learn advanced.